Scintigraphic results in patients with lung transplants - Humplik, B. I.; Sandrock, D.; Aurisch, R.; Richter, W.-St.; Ewert, R.; Munz, D. L. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: We addressed the feasibility of scintigraphy in the postoperative monitoring of lung transplants. Method: 37 patients (22 women, 15 men, 37 ± 15 years) in good clinical condition were examined after lung transplantation. Scintigraphic procedures for assessing ventilation (133Xe), perfusion (99mTc micro-spheres) and aerosol-inhalation (99mTc aerosol) were performed for all patients. The findings were compared with those of established diagnostic modalities. Results: All lung transplants showed homogeneous ventilation but with a non-physiologic difference of over 20% between both pulmonary lobes in one-third of the cases. There was a difference between the impairement of perfusion and ventilation in the presence of an impaired Euler-Liljestrand reflex in 14/37 (38%) patients. Furthermore, bronchoscopy and aerosol-inhalation scans often did not correlate, e. g. a bronchoscopically evident stenosis was not necessarily associated with an increased activity, and vice versa. Although peripheral mucociliary clearance was preserved after transplantation, stasis in central airways resulted in significantly impaired global clearance. Conclusion: Ventilation and perfusion scintigraphy reveal in a significant number of lung recipients pathologic findings and therefore can be recommended for postoperative monitoring. From a clinical point of view aerosol-inhalation scintigraphy (clearance) is not of any additional value.
Keywords: Lung scintigraphy; lung transplantation